2016
DOI: 10.1371/journal.pone.0165801
|View full text |Cite
|
Sign up to set email alerts
|

Use of Complementary and Alternative Medicine (CAM) as Part of the Oncological Treatment: Survey about Patients’ Attitude towards CAM in a University-Based Oncology Center in Germany

Abstract: IntroductionTo understand if and which patients would be open-minded to Complementary and Alternative Medicine (CAM) use parallel to their oncological treatment. Moreover, we sought to determine which methods are most accepted and which are the primary motivators to use CAM.MethodsWe developed and anonymously conducted a questionnaire for patients in the oncology center (TU Munich). Questions focus on different CAM methods, previous experiences, and willingness to apply or use CAM when offered in a university-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
67
1
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(81 citation statements)
references
References 47 publications
7
67
1
6
Order By: Relevance
“…Few patients only considered CM therapy to be used alone. Similar reported results supporting the patient's willingness to integrate CAM into their oncological therapy to be offered as a concomitant therapy [7]. Females had higher tendency to use CM in the current study (P=0.018).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Few patients only considered CM therapy to be used alone. Similar reported results supporting the patient's willingness to integrate CAM into their oncological therapy to be offered as a concomitant therapy [7]. Females had higher tendency to use CM in the current study (P=0.018).…”
Section: Discussionsupporting
confidence: 87%
“…ElNimr et al [4] reported that herbal medications are the most commonly (CM) used among adult Egyptians by (91.6%), similarly, the herbal therapy use was favored by 90.2% of the patients [12]. These findings are inconsistent with another study reported from countries like USA who commonly used dietary supplements [13], similarly the most preferred CM methods were vitamins/minerals and food supplements (42.3%) [7].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The use of CHA in cancer patients with conventional treatments such as chemotherapy, radiation and surgery is growing over the past 15 years, not only in Western countries, but also in the Far East or in developing countries. So it has undoubtedly gained medical, economic and research importance (Rossi et al, 2015, Kessel et al, 2016. Nevertheless the literature about CHA prevalence in cancer patients is not particularly rich.…”
Section: Discussionmentioning
confidence: 99%